Pemanfaatan Program Usaha Kesehatan Sekolah (UKS) Dalam Upaya Peningkatan Kesehatan Masyarakat di Sekolah Dasar Negeri Songkar - Ana Lestari; Rafi’ah Rafi’ah; Iga Maliga; Herni Hasifa (Jurnal Masyarakat Mengabdi Nusantara, 2023)
Implementation of School Health Efforts can improve health status and shape students' clean and healthy living habits. Therefore, School Health Efforts with an emphasis on promotive and preventive efforts supported by quality curative and rehabilitative efforts, are very important and strategic to achieve the highest degree of health. Currently, the partner's UKS room has its own room and is complete with first aid kits and medicines. However, there is still a lack of utilization programs and there are no UKS staff members who can immediately provide first aid when a student is in pain. The purpose of UKS is to improve the quality of education and student learning achievement through improving the behavior of a clean and spiritual life so that students can grow and develop harmoniously and optimally along with being independent in their activities and ultimately becoming quality human beings. This community service was held at Songkar Public Elementary School, North Moyo District in May 2023. There are two methods used in this community service activity, namely counseling about UKS, choosing peers as small groups and role playing.